Application Methods of Compost and Vermicompost for Suppressing Damping off Disease (Rhizoctonia solani) in Tomato Seedling - Istifadah, Noor; Baharudin, Aziz; Hartati, Sri (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2024)
Damping off caused by Rhizoctonia solani is an important soil-borne disease in tomato nursery. In addition to their role as organic fertilizer, compost and vermicompost are able to suppress plant diseases. Compos and vermicompost can be applied directly or in the form of their soaking water or teas. This study evaluated the abilities of compost, vermicompost, compost tea and vermicompost tea to inhibit R. solani in vitro and suppress damping off disease in tomato seedlings. The in vitro experiment used completely randomized design, while the experiment in tomato seedlings used randomized complete block design. The in vitro experiment examined nonsterile and sterile suspension or teas of compost and vermicompost. The treatments in tomato seedling experiment were compost or vermicompost applied in the growth media (25% v/v), compost or vermicompost tea applied to the tomato seedlings every 3 days or 7 days, and untreated check. The results showed that in the agar media containing suspension of compost or vermicompost nonsterile was dominated by Trichoderma spp. colonies and therefore the growth of R. solani was inhibited by 58.5-60.0%. The sterile preparation of compost, vermicompost and their teas did not inhibit the pathogen. Compost and vermicompost incorporated to the growth media suppressed damping off disease caused by R. solani by 54.2-66.7%. The abilities of compost and vermicompost to suppress the disease and support plant growth were better than their teas. Drenching the seedlings with compost tea every 3 or 7 days suppress damping off disease by 31.0-41.7%. However, vermicompost tea showed disease suppression (27.6-37.1%) only if it was applied every 3 days.